Exploring the Potential of Torulaspora delbrueckii, Starmerella bacillaris, and Saccharomyces cerevisiae as a Probiotic Starter for Craft Beer Production - Carmen-Rodica Vrînceanu; Filofteia Camelia Diguță; Mihaela Dragoi Cudalbeanu; Alina Ortan; Constanța Mihai; Iuliana Diana Bărbulescu; Mihai Frîncu; Mihaela Begea; Florentina Matei; Răzvan Ionuț Teodorescu (Foods)
This paper explores the broad probiotic and functional properties of two non-Saccharomyces strains (MI120 and MI125) and one Saccharomyces cerevisiae BB06 strain (as a reference probiotic). Torulaspora delbrueckii MI120 and Starmerella bacillaris MI125 were identified via 5.8S rDNA sequencing. All the strains survived well in simulated gastrointestinal conditions and had strong antioxidant activity (>68%). S. bacillaris MI125 excelled in antimicrobial activity against Gram-positive and Gram-negative bacteria. S. bacillaris MI125 and Sacch. cerevisiae BB06 resisted all the tested antibiotics. No strain displayed hemolytic behavior. The freeze-dried yeast strains achieved survival rates between 76.62% and 93.38%. Based on our physiological characterization analysis (carbon assimilation, ethanol tolerance, acetic acid and H2S production, temperature and low pH tolerance, enzymatic pattern, and killer phenotype), all the strains showed interesting attributes, with Sacch. cerevisiae BB06 fermenting vigorously in malt extract medium. Beer fermented with T. delbrueckii MI120 had the highest phenolic content (96.02 μg GAE·mL−1) and antioxidant activity (90.43%), matching commercial Sacch. cerevisiae US-05 in sensory traits such as taste and aroma. However, after two months in bottled beer, the yeast viability decreased to 2–3 log CFU·mL⁻1. The pilot brewing and the assessments of the strains’ technological, physico-chemical, and sensorial properties confirmed their suitability for industrial brewing. Overall, T. delbrueckii MI120 emerges as a promising brewing strain, and S. bacillaris MI125 is a potential probiotic.